Paladin's grace - Kingfisher, T. (Kingfisher, T. Saint of Steel, 2021)
"Stephen's god died on the longest day of the year ... Three years later, Stephen is a broken paladin, living only for the chance to be useful before he dies. But all that changes when he encounters a fugitive named Grace in an alley and witnesses an assassination attempt gone wrong. Now the pair must navigate a web of treachery, beset on all sides by spies and poisoners while a cryptic killer stalks one step behind"--Page 4 of cover